Oral health of brazilian older population: an integrative literature review (Research, Society and Development, 2021)
Over time, the human body undergoes a process of natural wear and tear due to aging. With oral cavity is no different and, unfortunately, edentulism still represents one of the main oral health problems inolder population. Aim: to review the scientific literature about oral health status of institutionalized and non-institutionalized older people in Brazil. Methodology: this is an integrative literature review, based on scientific articles indexed in the main health area databases in the last 10 years. The following keywords were used: “bucal”; “health”; “older”; “oral”; “condition”; “institutionalized”; “asylu” and descriptors: “oral health”; “elderly”; “aged”; “institutionalization”. Results: after applying the eligibility criteria, 2267 articles were retrieved, but only 8 were included in the review.It was observed that the brazilian older oral health condition is precarious, with high rates of DMFT and tooth loss.The aged institutionalized population also presents higher rates when compared to aged individuals in the community.Conclusion: the review in question confirmed that older brazilians have a worrying oral health condition, but institutionalization is associated with an even worse oral health condition, due to the vulnerability of these individuals. Thus, it is worth reflecting about health inequities imposed on this population and the need for public oral health policies specific to the aged population in Brazil.